Jeux de mots et créativité Langue(s), discours et littérature - Full, Bettina; Lecolle, Michelle (The Dynamics of Wordplay, 2018)
This volume seeks to shed light on the interdependencies between wordplay and language creativity. Contributions explore the most diverse genres and discourses throughout History -anagrams, medieval fatrasies, the works of Rabelais, children books, slam, riddles, and contemporary constrained writing-, trying to understand their theoretical, didactic and historical impact.